Effects of Sargassum oligocystum and Padina australis extract on adipogenesis and adipolysis in 3T3-L1 cells - Jaswir I.; Ahmad H.; Susanti D.; Bakhtiar M.T.; Octavianti F. (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS